Posterior reversible encephalopathy syndrome due to pulse methylprednisolone therapy in a child - İncecik, Faruk; Hergüner, M. Özlem; Yıldızdaş, Dinçer; Yılmaz, Mustafa; Mert, Gülen; Horoz, Özden O.; Altunbaşak, Şakir (The Turkish Journal of Pediatrics, 2013)
Posterior reversible leukoencephalopathy syndrome (PRES) is a recently described disorder with typical radiological findings of bilateral grey and white matter abnormalities in the posterior regions of the cerebral hemispheres. It has been described in children in association with some medications, renal disease, autoimmune disease, transplantation, and sepsis. In this report, we discuss an eight-year-old boy with PRES during pulse methylprednisolone therapy. In conclusion, PRES is a neurological complication of pulse methylprednisolone therapy, which responds favorably to prompt therapy withdrawal and blood pressure control.